Soluble triggering receptor expressed on myeloid cells 1 is associated with hemoconcentration and endothelial activation in children and young adults with dengue virus infection in the Philippines. - Jiayi Yang; Hridesh Mishra; Michelle Ngai; Vanessa Tran; Maria Salome Siose Painaga; James Yared Gaite; Ashley Roberts; Kevin C Kain; Michael T Hawkes (PLoS Neglected Tropical Diseases)
Background Triggering receptor expressed on myeloid cells 1 (TREM1) is a cell-surface receptor expressed on neutrophils that amplifies the inflammatory response. Dengue virus (DENV) infection is characterized by systemic inflammation, endothelial activation, and vascular leakage. Methodology/principal findings We investigated circulating soluble TREM-1 (sTREM-1) levels in 244 children and young adults aged 1-26 years with dengue fever presenting to an outpatient clinic in the Philippines. Elevated sTREM-1 (≥130 pg/mL) was associated with hemoconcentration, a hallmark of vascular leakage (odds ratio (OR) 3.8, 95%CI 1.6-10, p = 0.0020). In turn, hemoconcentration was associated with hospitalization (OR 4.2, 95%CI 1.0-38, p = 0.0497) and higher volume of intravenous fluid required for resuscitation (p = 0.019). Elevated inflammation marker TNF (≥5 pg/mL) was associated with increased sTREM-1 levels (p = 0.0014). Endothelial activation markers angiopoietin-2 (Ang-2), soluble FMS-like tyrosine kinase-1 (sFlt-1), and soluble vascular cell adhesion molecule 1 (sVCAM-1) were correlated with sTREM-1 levels (p < 0.0001 for all three comparisons). Conclusions/significance Our findings suggest that sTREM-1 may be a clinically informative marker of neutrophil activation, associated with hemoconcentration, systemic inflammation, and endothelial activation and in dengue fever.